Strengthening Moral Education Values: Sociological Analysis of the Mbah Sholeh Haolan at Pesantren Benda Kerep, Cirebon - Rusmana, Dadan; Rosidin, Didin Nurul; Saefullah, Asep; Burhanudin, Dede; bin Zainuddin, Ghazali (Ulumuna, 2024)
This article explores the role of Mbah Sholeh haolan (commemoration) in strengthening Islamic education in Benda Kerep Village. This event serves as a cornerstone for cultural preservation, intergenerational learning, and practical implementation of Islamic values. The kyai, or spiritual leaders, play a pivotal role in guiding the community, reinforcing their authority and the respect they command. The haolan facilitates social cohesion, fosters a strong sense of identity, and exemplifies the community’s commitment to Islamic teachings. By examining the significance of Mbah Sholeh haolan, the article provides insights into how traditional Islamic communities can navigate the challenges of modernity while preserving their religious and cultural heritage. This study show that commemoration is one of the means used to pass on the cultural and religious values contained in "Wasiat Sepuh" as one of the character education and character-building. Kyai is the central figure, the foremost patron, followed by the community, so what Scott calls a patron-client cluster is formed. Kyai in Benda Kerep serves as an information leader who, in many ways, trumps the role of formal government officials. Kyai serves as the community's protector, a place to seek advice, and the final decision-maker on various problems in the area.